Effectiveness of Group Guidance Cognitive Behavior Therapy (CBT) Approach with Bibliotherapy Technique to Develop Healthy Sexual Behavior in Adolescents - Feni Listari; Netrawati; Zadrian Ardi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to further optimize the services provided by looking at the effectiveness of group guidance with a CBT approach using bibliotherapy techniques to develop healthy sexual behavior in teenagers at SMA Negeri 1 Tebing Tinggi. Of the several approaches and counseling techniques, one approach that is considered suitable for developing healthy sexual behavior in adolescents is using the bibliotherapy technique. revealed that bibliotherapy can be used for a variety of problems faced by clients, including illness, death, self-destructive behavior, family relationships, identity, violence and abuse, race and prejudice, sex and sexuality and gender.